Analisis Pendidikan Karakter Disiplin melalui Pembiasaan Pada Siswa Sekolah Dasar - Dewi Wulandari; Yuyun Yulia; Banun Havifah Cahyo Khosiyono; Titik Mutiah (Perspektif Pendidikan dan Keguruan, 2023)
The background for the implementation of this research is the existence of disciplinary character education for students through habituation activities at school so that by instilling disciplinary character education it can discipline students more, both at school, at home, and in society. This research was conducted with a qualitative approach. This study aims to analyze and describe the implementation of disciplinary character education through habituation in elementary school students. This research was conducted with a qualitative approach. The research was conducted at SD Negeri Ngringin Moyudan, Sleman. The research subjects are school principals, teachers, and students. Observations, interviews, and documentation are used as data in this study. The technique of checking the validity of the data uses a triangulation technique. The results showed that in instilling disciplined character education through habituation at Ngringin Public Elementary School, namely 1) creating a character education program; 2) making school rules and class agreements; 3) making a liaison book for monitoring student disciplinary behavior at home; 4) providing moral messages on the walls of schools and classrooms; 5) involving parents/guardians of students in disciplinary character education; and 6) involving school committees in disciplinary character education.